PELATIHAN VISUAL STUDIO PADA ANGGOTA MASYARAKAT PAJANG - ketut, Ketut Widya Kayohana (CV SWA Anugerah, 2024)
This activity is organized and implemented by the Bumigora University Social Charity Team, which was formed with the goal of improving the quality of human resources in line with the technological developments of the era of globalization of Industry 5.0. Untuk pelapan tujuan tersebut, dinningan persining alat baasar Arduino microcontroller di minglinger Pajang. In the training process, participants will get basic knowledge about electronic engineering tools, visual coding, computer science, and robotics. In addition, this training can increase the creativity of participants in creating various types of electronic devices using visual codes. Through this activity, the microcomputer training received very positive feedback from the participants, and was able to increase the knowledge of the training participants who did not have enough knowledge in the field of electronics